Psychological Effect of Customers to The Re-Purchase Decision of AirBNB Accommodation Facilities in Jakarta - Asep Parantika; RR. Cindy Diana Nadia Lolita (Media Wisata, 2021)
Attitude repurchase decision influenced by other three components, which are stay experience. This article aims to discover the psychological effect of customers’ service on the re-purchase decision of AirBNB accommodation facilities in Jakarta. The research uses quantitative analysis. The data collection technique used is questionnaire circulation and literature reviews. The result shows that there are three components influencing respondents to reuse AirBNB services, which are Motivation, Perception, and, Users Review, and Price Sensitivity. Every component provides each influence in determining the repurchase decision of Air bnb. Service psychology holds a great impact on the AirBNB repurchase decision. Other components such as motivation, perception, and attitude play significant roles in the decision and greatly impacted the customers, as well as other factors such as stay experience, guest review and price sensitivity.